(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Stature is a important factor in identification of an unidentified dead body or any mutilated part of such body. In present study we made an attempt to estimate the stature from percutaneous length of ulna. Study consists of 94 adult males and 96 adult females between the age group of 18- 24 years, born and brought up in Maharashtra. The length of the of the right and left ulna was measured with a venier calliper from the apex of the olecranon to the styloid process and the height of the individual was measured with a calibrated standing meter rule. The measurements were noted in the proforma. The data was statistically analyzed and linear regression formulae were derived.